2016
DOI: 10.1039/c6ay02087a
|View full text |Cite
|
Sign up to set email alerts
|

A novel molecularly imprinted electrochemiluminescence sensor based on a Ru(bpy)32+/MWCNTs/nano-TiO2-Nafion electrode for the detection of bisphenol A

Abstract: A novel molecularly imprinted electrochemiluminescence sensor based on a Ru(bpy)32+/MWCNTs/nano-TiO2-Nafion electrode was successfully designed for ultrasensitive and ultraselective detection of BPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…One approach is the incorporation of the electroluminescent species into the electrode itself [91]. They prepared a [Ru(bpy) 3 ] 2+ /MWCNTs/nano-TiO 2 -Nafion electrode on which the MIP selective to bisphenol A was deposited.…”
Section: Bi-dimensional Compositesmentioning
confidence: 99%
“…One approach is the incorporation of the electroluminescent species into the electrode itself [91]. They prepared a [Ru(bpy) 3 ] 2+ /MWCNTs/nano-TiO 2 -Nafion electrode on which the MIP selective to bisphenol A was deposited.…”
Section: Bi-dimensional Compositesmentioning
confidence: 99%
“…Those nanomaterials with outstanding quantum efficiencies can be directly fabricated and employed as promising ECL emitters for signal transduction or image probing. For those nanomaterials with large specific surface areas or porous nanostructures, such as mesoporous silica nanospheres (MSNs) [10][11][12][13], multiwall carbon nanotubes [14][15][16], graphene oxide [17][18][19][20], Ti 3 C 2 MXene [21][22][23], and Au nanoparticles (NPs) [24], they can be utilized as the carriers to stabilize luminophores and developed as ECL emitters for biosensors. Unlike self-annihilation ECL pathway, a proper coreactant reagent is essentially required for coreactant ECL since it can generate abundant electro-active intermediates to promote the production of excited states, thus achieving stronger ECL intensity [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al developed a new MIP-ECL sensor based on MWCNTs/nano-TiO 2 nanocomposite for BPA detection. 31 Necip Atar et al proposed a MIECL sensor of atrazine by employing Pt nanoparticle/C 3 N 4 nanotube nanocomposites as the sensor carrier. 32 Bahareh Babamiri et al reported a MIECL sensor which used GO–Fe 3 O 4 composites as the sensing platform for the detection of creatinine.…”
Section: Introductionmentioning
confidence: 99%